Entrepreneurship education and the propensity for business creation: testing a structural model. (2nd December 2009) - Rodrigues, Ricardo G.; Raposo, Mario; Ferreira, Joao; Do Paco, Arminda
This study aims to identify the factors that contribute the most to the intention to start up a business. The research also aims to identify the profile of student who is a potential entrepreneur concerning several aspects: personal attributes, family, demographic variables and motivations. Based on a sample of university students, a structural model was tested. Research findings include the idea that entrepreneurship education is the most relevant factor in the propensity for business creation. On the other hand, personal characteristics have an important role in shaping the motivation to start up a business and perceived hurdles have a negative impact on the intention to start one up.